«FOUR – “I”» MODEL: LEVELS OF INTEREST DEVELOPMENT IN TEACHING PROFESSION - Merkulova , Svitlana (The Modern Higher Education Review, 2022)
The article is devoted to the study of different approaches to obtaining a teaching profession and considering development of interest in teaching profession. Choosing development of interest in teaching profession as the object of this article, the author intends to compare different approaches and interpretations of the above term in educational process and professional orientation. Changing in teaching profession standards and new challenges of time became the basis for new approach to the process of professional orientation and caused additional study of the latest generation called Post- Millennials or Zoomers in different sources. Analysis of the latest generation characteristics by different scientists and research groups became the basis of rethinking previous experience in teaching profession orientation of high school students. Changes in life environment, new approaches to education process, new generation grown up are taken into account in current study. As a result, a «Four – “I”» model: Levels of Interest development in teaching profession” is created and signs of interest in teaching profession were specified for Zoomers. Additionally, six indicators of interest development in teaching activity are determined to clarify further teaching profession orientation process.